Comparative In Vitro and In Silico Enzyme Inhibitory Screening of Rosa x damascena and Pelargonium graveolens Essential Oils and Geraniol - Karadag, Ayse Esra; Biltekin, Sevde Nur; Demirci, Betul; Demirci, Fatih; Ghani, Usman (Mdpi, 2023)
The present work aims to evaluate Rosa x damascena Herrm. and Pelargonium graveolens L'Her. essential oils, and the major constituent geraniol for their in vitro and in silico inhibitory activities against 5-lipoxygenase (5-LOX), cyclooxygenase (COX), acetyl cholinesterase (AChE), butyryl cholinesterase (BuChE), and angiotensin converting enzyme (ACE2) enzymes. Geraniol most potently inhibited the ACE2 relative to other enzymes. R. damascena essential oil moderately inhibited the cancer cell lines with no toxic effects on healthy HEK 293 cells. P. graveolens essential oil inhibited a number of cancer cell lines including A549, MCF7, PC3, and HEK 293 that are reported here for the first time. The molecular docking of geraniol with the target enzymes revealed that it binds to the active sites similar to that of known drugs. Geraniol carries the potential for further drug development due to its drug-like binding mode for the target enzymes. Our work confirms that these essential oils possess similar biological activities due to their similar phytochemistry in terms of the major constituents of the plants. The promising biological activities reported in this work further warrant the inclusion of in vivo studies to establish safe use of the target essential oils and their constituents.
Keywords: angiotensin converting enzyme II; cholinesterase; cyclooxygenase; lipoxygenase; cytotoxicity